Susceptibilidade erosiva do baixo curso do rio Acaraú-CE - Diniz, Simone Ferreira [UNESP]; Moreira, César Augusto [UNESP]; Corradini, Fabrício Aníbal [UNESP] (My University, 2008)
The inadequate land use in the low course of the river Acaraú is speeding up processes of erosion in some degrees. This process is accented in the areas where caatinga was removed for implantation of pastures and agriculture. Concomitantly, the plain of flooding of the river Acaraú an accumulation of sand with the carry of these sediments, resulting in the widening of the fluvial plain and reduction of the shape water, with increase of the evapotranspiration and consequence salinization, proceeding from the local substratum. This paper aimed at the crossing of diverse space information (geomorfology, soil, declivity, geology and land use) in environment SIG, for determination of the susceptible areas to the erosion and an accumulation of sand in the low course of the Acaraú river, north of the State of the Ceará, Brazil. The results allow to evaluate the application of this tool in the planning and management of the environment, from the crossing of the type of use with the used environment and the consequent impact to the ecosystem.

O uso inadequado do solo no baixo curso do rio Acaraú está acelerando processos de erosão em vários graus. Este processo é acentuado nas áreas onde a caatinga foi removida para implantação de pastagens e agricultura. Concomitantemente, a planície de inundação do rio Acaraú é assoreada com o transporte de sedimentos, resultando no assoreamento da planície fluvial e redução da espessura da lâmina d’água, com aumento da evapotranspiração e conseqüente salinização, proveniente do substrato local. Este trabalho visou o cruzamento de diversas informações espaciais (geomorfologia, solo, geologia, uso do solo, elevação e declividade) em ambiente SIG, para determinação das áreas susceptíveis à erosão e assoreamento no baixo curso do rio Acaraú, norte do Estado do Ceará, Brasil. Os resultados permitiram avaliar a aplicação desta ferramenta no planejamento e gestão do meio físico, a partir do cruzamento do tipo de uso com o ambiente utilizado e o conseqüente impacto ao ecossistema. Palavras-chave: susceptibilidade erosiva, assoreamento, SIG, baixo curso do rio Acaraú, Estado do Ceará.
Erosive suceptible in low course of Acaraú river-CE
Keywords: Ceará state; Erosive suceptible; GIS; Lower course Acaraú river; Sedimentation; caatinga; erosion; evapotranspiration; fluvial deposit; land use; pasture; river; salinization; sediment transport; sedimentation; Acarau River; Brazil; Ceara; South America